Lumberjanes. Friendship to the max - Stevenson, Noelle; Ellis, Grace; Allen, Brooke A.; Watters, Shannon (Los Angeles, CA : BOOM! Box, a division of Boom Entertainment, Inc., 2015)
Jo, April, Mal, Molly, and Ripley are not your average campers and Miss Quinzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady-types is not your average summer camp. Between the river monsters, magic, and the art of friendship bracelets, this summer is only just beginning. Join the Lumberjanes as they take on raptors and a sibling rivalry that only myths are made of.
Originally published in single magazine form as Lumberjanes No. 5-8.
Created by Shannon Watters, Grace Ellis & Noelle Stevenson.
School Library Journal starred, October 2015
Booklist, December 2015
3.4
5-8
Keywords: Teenage girls -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Camps -- Fiction; Monsters -- Fiction; Adventure and adventurers -- Fiction; Horror stories; Teenage girls -- Comic books, strips, etc -- Fiction; Friendship -- Comic books, strips, etc -- Fiction; Camps -- Comic books, strips, etc -- Fiction; Monsters -- Comic books, strips, etc -- Fiction; Action and adventure comics; Horror comics; Graphic novels; LGBTQ+ fiction; Comics (Graphic works)